Edukasi Kebersihan Diri (Personal Hygiene) pada Anak untuk Meningkatkan Kebersihan Diri Anak - Suprobo, Nina Rini; Putri Novembriani, Rizqie; Danik Kurniawati, Elisa; Kirana Hasanah , Winny (Universitas Nusantara PGRI Kediri, 2022)
School children are at a golden age to teach the values of clean and healthy living behavior, which have the potential to become agents of change in socializing clear and healthy living behavior in the school, family and community environment. The COVID-19 crisis highlights the need to increase health literacy. Schools should act as health promoters for their students from an early age, by actively fostering healthy habits (physical activity, good personal hygiene, and a balanced diet) and raising awareness of the consequences of risky behavior. Proper personal hygiene knowledge and practices play an important role in avoiding communicable diseases and allowing primary school children to enjoy a healthy and productive school life. The purpose of this activity is to improve the health of early childhood by teaching personal hygiene to children.